The survey effectiveness of career counseling based on the native model of work-family enrichment on the facilitation of family-work conflict and fundamental self-evaluation in Women employees of Isfahan University - farshid aslani; marziyeh malekiha (فصلنامه زن و جامعه, 2023)
Aim:The aim of this research was the survey effectiveness of career counseling based on the native model of work-family enrichment on the facilitation of work-family and family-work conflict. Method:The research method was quasi-experimental method where in the pre-test and post-test were used with experimental and control group. The stastisical population were all of female workers in Isfahan University at 2021. From this population 30 persons were selected from the list of voulentary person who ready to participate and were substituted randomly in to experiment group (15 person) and control group (15 person).The independent variable was the career counseling sessions based on the model of work-family enrichment (Greenhous & Powell, 2006) that have been performed in 8 sessions to the experiment group and control group did not any intervention. In this research were used from demographic and work-family conflict (McMarian & Net Mayer, 1996) questionnaires for data gathering. Results: results of Analysis of Covariance (ANCOVA) showed that there is meaningful difference between means post-test of experimental and control group in two demintion of work-family enrichment and family-work enrichment (P<0.05).Conclusion:career counseling base on the native model of work-family enrichment is effective in facilitate of work-family conflict in two dimensions.